PLC basic simulator / Muhammad Hanif Al-Hawari Al-Malek Faseh & Fatin Natasha Ismail - Al-Malek Faseh, Muhammad Hanif Al-Hawari; Ismail, Fatin Natasha (2015)
In this final year project, this project was designed based on the idea of the PLC system. Programmable Logic Controller (PLC) is common process controller used in the industry area. The PLC is also considered as a specific computer that capable of performing many functions automatically. In study of electrical, the students will learn about the PLC system. But most of the students don't know how to apply the PLC system in real life. Thus, in this project helps the users apply the basic knowledge of PLC in PLC Basic Simulator. The mnemonic code is a programming language in PLC. The code depends on the PLC used but normally from one PLC to another there is not much difference. If the students are an expert in developing a programmer using one type of PLC, it is not difficult to understand the programming concept of any other PLC. This project is based on mnemonic structure of coding PLCs for the students will know how to use the PLC in real life. This project mainly describe about how to enable the users to read and understand the Programmable Logic Controller (PLC).